A removable virus vector suitable for plant genome editing. (6th June 2017) - Chujo, Tetsuya; Yoshikawa, Manabu; Ariga, Hirotaka; Endo, Masaki; Toki, Seiichi; Ishibashi, Kazuhiro
Summary: Plant genome editing is achieved by the expression of sequence‐specific nucleases (SSNs). RNA virus vector‐mediated expression of SSNs is a promising approach for transgene integration‐free targeted mutagenesis in plants. However, the removal of virus vectors from infected plants is challenging because no antiviral drugs are available against plant viruses. Here, we developed a removable RNA virus vector that carries the target site of tobacco microRNA398 (miR398) whose expression is induced during shoot regeneration. In the inoculated leaves in which expression of miR398 is not induced, insertion of the miR398 target site did not affect the practicability of the virus vector. When shoots were regenerated from the infected leaves, miR398 was expressed and viral RNA was eliminated. The virus vector successfully expressed SSNs in inoculated leaves, from which virus‐free genome‐edited plants were regenerated via tissue culture. Significance Statement: Here we developed a removable tomato mosaic virus vector by inserting the target sequence of an inducible host endogenous microRNA. Expression of a sequence‐specific nuclease using the virus vector in tobacco leaves followed by removal of the virus vector from regenerated genome‐edited shoots was demonstrated.